PENGARUH EMPLOYER BRANDING TERHADAP MINAT GENERASI Z DALAM MEMILIH TEMPAT KERJA - Priatna Kesumah (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
Employer branding plays a crucial role in attracting Generation Z’s interest in choosing a workplace. This generation has different preferences from previous generations, with a tendency to be more selective in considering aspects such as work culture, flexibility, employee well-being, and career development opportunities. This study aims to analyze the influence of employer branding on Generation Z’s interest in choosing a workplace and identify the branding elements that have the most significant impact. This research employs a quantitative descriptive approach, with data collected through surveys targeting respondents categorized as Generation Z. Data analysis was conducted to examine the relationship between employer branding and Generation Z’s interest in selecting a workplace, as well as to identify the key factors influencing their decisions. The results indicate that strong employer branding enhances a company's attractiveness and influences Generation Z’s decision in choosing a workplace. Factors such as work flexibility, transparency in career progression, and corporate values aligned with their expectations play a significant role in shaping their interest in employment. Keywords: Employer branding , Generation Z, job interest, corporate image, work flexibility.